2005
DOI: 10.1016/j.jaap.2004.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanocrystalline HZSM-5 external surface on the catalytic cracking of polyolefins

Abstract: Catalytic cracking of both LDPE and HDPE has been studied using three different samples of nanocrystalline HZSM-5 zeolite as catalysts. The zeolite samples were synthesized under different conditions in order to obtain materials with different crystal sizes in the nanometer range (10-60 nm) and high external surface areas (78-242 m 2 /g). The plastic cracking reactions were carried out at 340 8C for 2 h using a plastic/ catalyst mass ratio of 100. Despite these really mild conditions, high activities were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 16 publications
1
57
0
Order By: Relevance
“…The use of zeolites has been shown to be effective in improving the quality of products obtained in the pyrolysis of polyethylene and other addition polymers. The acidity of their active sites and its crystalline microporous structure (textural properties) favor hydrogen transfer reactions and thereby make them suitable for obtaining high conversions of gas at relatively low temperatures, between 350 and 500 °C [11,18,22,[41][42][43][44] . That is, these features allow milder operating conditions (lower temperatures and reaction times) than a thermal pyrolysis [4,25,30,45] .…”
Section: Catalytic Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…The use of zeolites has been shown to be effective in improving the quality of products obtained in the pyrolysis of polyethylene and other addition polymers. The acidity of their active sites and its crystalline microporous structure (textural properties) favor hydrogen transfer reactions and thereby make them suitable for obtaining high conversions of gas at relatively low temperatures, between 350 and 500 °C [11,18,22,[41][42][43][44] . That is, these features allow milder operating conditions (lower temperatures and reaction times) than a thermal pyrolysis [4,25,30,45] .…”
Section: Catalytic Pyrolysismentioning
confidence: 99%
“…This determines the products obtained in these reactions. Solid acid catalysts such as zeolites, favor hydrogen transfer reactions due to the presence of many acid sites [11,18,22,36,42,44] . The acid strength of the solid is characterized by the presence of Lewis or Brønsted acid sites.…”
Section: Catalytic Pyrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Botella et al [42] reported the Beckmann rearrangement reaction over nano-beta zeolite, where the reactions proceed mainly on the external surface of the zeolite. Serrano et al [43] reported catalytic cracking of polyolefins over nano-ZSM-5 zeolite. Because the molecular size of polyolefins is larger than the pore size, cracking of polyolefins occurs mainly over the acid sites on the external surface, followed by the -20-formation of lighter olefins on the internal pore surface.…”
Section: Catalytic Reactionmentioning
confidence: 99%
“…[38] Acid sites in zeolites (particularly beta) catalyze the pyrolysis of polyethylene, allowing operation at lower temperatures with respect to thermal pyrolysis, as well as a higher selectivity toward the desired products. [39][40][41][42] In plastic degradation, it is known that both Lewis and Brønsted acid sites are involved in the initial step of the LDPE degradation, by hydride abstraction of the polymer or by the addition of a proton to a C-C bond, respectively. [39] The polyethylene molecule suffers successive b-scissions, producing fragments with lower molecular weights.…”
Section: Ldpe Pyrolysismentioning
confidence: 99%